A feasibility study on additive manufactured hybrid metal/composite shock absorbers. (15th July 2021) - Acanfora, V.; Saputo, S.; Russo, A.; Riccio, A.
Abstract: Commonly adopted shock absorbers and, in general, crashworthy structural components, based on sandwich structural concepts and/or complex dumping mechanisms, are, generally, characterized by high volumes and significant additional mass. This research activity is focused on the investigation of the feasibility and effectiveness of novel thin additive manufactured hybrid metal/composite lattice structures as lightweight shock absorbing devices for application to structural key components in impact events. These hybrid structures would represent a real step beyond the state of the art of shock absorbers being characterized by an additive manufactured metal lattice core, able to maximize the absorbed energy by plastic deformations and, at the same time, by a composite skin/cohesive coating, fully integrated with the internal metal lattice structure, able to lower the global weight and increase the stiffness and strength of the shock absorber. First, an extensive explicit numerical activity has been performed finalised to the assessment of the mechanical behaviour of basic lattice Unit Cells configurations under impact conditions in shock-absorbing panels. The variation of the geometrical characteristics of the lattice cells have been taken into account by adopting a parametric Python routine in ABAQUS with a simplified FEM formulation based on beam and shell elements. Once identified the key features maximizing the energy absorption capabilities of the metallic core, several complex models with 3d solid element formulation have been developed. A final comparison between the hybrid configurations and the state of the art shock absorbing panels, demonstrated the effectiveness of the proposed lightweight hybrid configuration based on additive manufacturing techniques in terms of mass reduction, mechanical and energy absorption performances.